Examining the Attitudes and Adoption Level of E-Learning Among UUM's International Postgraduate Students - Swidan, Mohamed El-Mabrouk (2007)
Nowadays, many education institutious especially universities, have widened access to their courses through new methods of delivery, specifically via electronically mediated learning, or e-learning. Although online learning clearly has a growing presence in higher education, discussions about implementing e-learning continue to lack consensus. Universiti Utara Malaysia has established the use of e-learning system; however, the actual information of the e-learning implementation in Universiti Utara Malaysia remains unclear. It is imperative to evaluate the study and find out the postgraduate perspective on the e-learning implementation in the university itself. By investigating the international postgraduate experiences of those implementing e-learning, our aim is to inform on e-learning and to pick some of the reality of e-!earning environment university. Knowing exactly how international postgraduate students feel about educational technology will permit to manage the psychological aspects of the process and offer motives for the adoption and use of educational technology. In our study, we determined the type of applications students used in e-learning and the adoption levels of e-learning among the students. We also examined the international postgraduate attitudes towards e-learning and the relationships between attitudes and adoption. Four hundred and seventy one international postgraduate students participated in this study. A research survey was carried out in University Utara Malaysia (UUM) by using a questionnaire method to collect data. Our results were statistically analyzed with SPSS by using paired t-test. From our study, we found that the international postgraduate students at UUM Malaysia have been exposed to some parts of the features offered by UUM Online system. However, many students are still not making full use of the features offered by UUM e-learning system. It is advisable to conduct further studies in the future to determine the functionality of the UUM e-learning system and the methods to overcome these reasons.